A Comparison of the Malignancy Incidence Among Patients With Psoriatic Arthritis and Patients With Rheumatoid Arthritis in a Large US Cohort. Issue 6 (June 2014) - Gross, Rachael L.; Schwartzman‐Morris, Julie S.; Krathen, Michael; Reed, George; Chang, Hong; Saunders, Katherine C.; Fisher, Mark C.; Greenberg, Jeffrey D.; Putterman, Chaim; Mease, Philip J.; Gottlieb, Alice B.; Kremer, Joel M.; et al.
<x xml:space="preserve">Abstract</x> Objective To compare the incidence rates of malignancy among patients with psoriatic arthritis (PsA) and patients with rheumatoid arthritis (RA) in the Consortium of Rheumatology Researchers of North America (CORRONA) registry. Methods We analyzed 2, 970 patients with PsA (7, 133 patient‐years of followup) and 19, 260 patients with RA (53, 864 patient‐years of followup). Using a standardized adjudication process, we identified 40 confirmed malignancies in the patients with PsA and 307 confirmed malignancies in those with RA. Incidence rates were calculated per 100 patient‐years. Incidence rate ratios were estimated, with adjustment for age, sex, disease duration, body mass index, disease activity, year of enrollment, and medication use. Results The overall malignancy incidence per 100 patient‐years was similar between patients with PsA and patients with RA (0.56 [95% confidence interval (95% CI) 0.40−0.76] and 0.56 [95% CI 0.50−0.63], respectively). Nonmelanoma skin cancer was the most common type of cancer in the overall cohort, with an incidence rate of 0.21 (95% CI 0.12−0.35) in PsA, and 0.20 (95% CI 0.17−0.24) in RA, with a calculated incidence rate ratio of 1.05 (95% CI 0.61−1.80; P = 0.85). Lymphoma rates were similar in PsA and RA (0.04 [95% CI 0.01−0.12] and 0.04 [95% CI 0.02−0.06], respectively; incidence rate ratio 1.00 [95% CI 0.17−3.11]; P = 0.67). The adjusted incidence rate ratio of malignancy in PsA versus RA was 1.17 (95% CI 0.82−1.69; P = 0.37). Conclusion The incidence rates across malignancy subtypes were similar in the PsA and RA cohorts from a US registry.